Expert-based approach on mapping ecosystem services potential supply in circling a protected areas by integrating matrix model assessment - Kamlisa Uni Kamlun; Renate Bürger Arndt (IOP Publishing Ltd, 2019)
The concept of ecosystem services was introduced into global policy to consolidate both conservation and development to interconnect the discourse between biodiversity and sustainable development for the benefit of human well-being; this encourages conservation and land use planners to achieve both ecological and social goals. Mapping the potential supply of ecosystem services is necessary for continuous monitoring of such services to ensure the sustainable management of natural resources to support decision-making. Therefore, this study presents a multifaceted methodological framework for mapping ecosystem services potential supply surrounding a protected area. We integrate a non-monetary ‘Matrix Model’ assessment with an expert-driven approach to assess the potential supply from a holistic perspective. Experts and stakeholders dealt with Likert scales to weigh multiple land cover supply of ecosystem services. Our study shows that using an integrated approach to map ecosystem services not only minimizes uncertainties but is also important for the evaluation of ecosystem services. The integration process can also be an interactive approach between scientists and stakeholders to improve mutual understanding regarding resource management. The selected services and land cover data can be an effective medium to visually exhibit forest function and the services of a protected area; these can work as scheming tools that can contribute to an effective policy measurement for the sustainable conservation of protected areas.